Mainstreaming agro-climatic advisory with crop-nutrient recommendations for 5,756 Filipino rice farmers in the Bicol region - Girly Balanza , Jane; Wei, Xiaojing; Swaans, Cornelis (2024)
By the end of 2024, the Bioversity-CIAT Alliance delivered 20,576 agro-advisories via SMS to more than 5,756 rice farmers, enhancing their ability to adapt to changing climate conditions and improve crop productivity [5]. In collaboration with the International Rice Research Institute (IRRI) the Alliance successfully integrated the Agro-Climatic Advisory Portal (ACAP) with the Rice Crop Manager Advisory Service (RCMAS) in the Bicol region under the CGIAR Climate Resilience Initiative. This provided near real-time weather forecasts and tailored nutrient management recommendations.